Introduction to Nano Basics to Nanoscience and Nanotechnology - Sengupta, Amretashis.; Sengupta, Amretashis.; Sarkar, Chandan Kumar.; Sarkar, Chandan Kumar. (Engineering Materials,, 2015)
This books covers the basics of nanotechnology and provides a solid understanding of the subject. Starting from a brush-up of the basic quantum mechanics and materials science, the book helps to gradually build up understanding of the various effects of quantum confinement, optical-electronic properties of nanoparticles, and major nanomaterials. The book covers the various physical, chemical and hybrid methods of nanomaterial synthesis and nanofabrication as well as advanced characterization techniques. It includes chapters on the various applications of nanoscience and nanotechnology. It is written in a simple form, making it useful for students of physical and material sciences.